1988
DOI: 10.1111/j.1600-0560.1988.tb00557.x
|View full text |Cite
|
Sign up to set email alerts
|

Reactive and malignant “angioendotheliomatosis”: a discriminant clinicopathological study

Abstract: In order to determine whether or not phenotypic differences existed between reactive angioendotheliomatosis (RAE) and malignant angioendotheliomatosis (MAE), we studied the histological and immunohistochemical features of 4 and 8 cases of these lesions, respectively. Antibodies to leukocyte common antigen (LCA), specialized B- and T-lymphocytic determinants, Factor VIII-related antigen (FVIIIRAG), blood group isoantigens A, B, and H (BGI), epithelial antigens, vimentin, and actin; and Ulex europaeus I lectin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0
10

Year Published

1993
1993
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(58 citation statements)
references
References 25 publications
3
45
0
10
Order By: Relevance
“…Neoplastic cells may also be found outside the vasculature [3, 18]. Intraluminal fibrin deposition and/or thrombi may be seen which, along with neoplastic cells, lead to occlusion of blood vessels producing infarcts of affected tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neoplastic cells may also be found outside the vasculature [3, 18]. Intraluminal fibrin deposition and/or thrombi may be seen which, along with neoplastic cells, lead to occlusion of blood vessels producing infarcts of affected tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathologically, the differential diagnosis for IL includes other entities showing intravascular proliferation, especially reactive angioendotheliomatosis (RAE) [18]. RAE is a much rarer, self-limiting condition characterized by a proliferation of endothelial cells within vascular lumina.…”
Section: Discussionmentioning
confidence: 99%
“…Bei der malignen Angioendotheliomatose bestehen die Proliferate aus atypischen mononukleären Zellen mit zahlreich vorkom− menden Zell− und Kernatypien, die in den meisten der bisher publizierten Fälle als B−Lymphozyten klassifiziert werden konn− ten [6,21]. Neben diesen intravasalen oder angiotropen B−Zell− Lymphomen wurden nur sehr vereinzelt T−Zell−Lymphome oder histiozytische Lymphome diagnostiziert [11,22,23].…”
Section: Histopathologischer Befundunclassified
“…Positive Markierun− gen der intravasalen Proliferationen mit Endothelzellmarkern, z. B. mit UEA1, sowie der Nachweis muskelaktin−besetzter peri− vasaler Perizytenmanschetten belegen hingegen das Vorliegen einer reaktiven Angioendotheliomatose [21]. Die Ätiopathoge− nese der Angioendotheliomatosen ist weitgehend ungeklärt.…”
Section: Histopathologischer Befundunclassified
“…The nosologic term IML replaced angiotropic lymphoma tosis, because 'angiotropic' may be confused with 'angiotrophic' [1], as well as malignant angioendotheliosis (MAE), after it was demonstrated that the malignant cells are of lymphoid rather than endothelial origin (as initially Accepted: February 15. 1995 thought), since they stain positive for lymphoid cell mark ers (leukocyte common antigen) but not for endothelial cell factor VUI-related antigen [2,3], IML bears a poor outcome and should be differentiated from reactive angiocndotheliosis (RAE), which implies milder forms (gen erally limited to skin involvement) and a better prognosis [4], The diagnosis of IML is histological; clinical criteria are not defined, and with time, new clinical manifesta tions are reported. The first communications emphasized the maculopapular eruption of skin over the limbs and trunk; after a few years, systemic and neurological fea tures were also reported.…”
Section: Introductionmentioning
confidence: 99%